Ligand-based control of nuclearity in (NHC)gold(i) sulfides. Issue 43 (26th October 2021) - Sato, Christopher M.; Walde, Rebecca K.; Bacsa, John; Jordan, Abraham J.; Sadighi, Joseph P.
Abstract : N-Heterocyclic carbene ligands allow selective synthesis of terminal or bridging hydrosulfides, and doubly or triply bridging sulfides, depending on sterics. Abstract : N-Heterocyclic carbene (NHC) ligands support gold(i ) sulfide complexes of varying nuclearity and charge. For sterically undemanding ligands, gold(i ) chlorides react with sulfide to form trigold μ3 -sulfido cations as the first observed products. The ligand IMes [1, 3-bis(2, 4, 6-trimethylphenyl)imidazol-2-ylidene] supports a monomeric cation, whereas the ICy-(1, 3-dicyclohexylimidazol-2-ylidene-) supported cation crystallises as a dimer linked through an aurophilic interaction. The more sterically demanding IDipp [1, 3-bis(2, 6-diisopropylphenyl)imidazol-2-ylidene] supports a terminal hydrosulfide, a (μ-hydrosulfido)digold cation, and a μ3 -sulfido cation. Use of the expanded-ring NHC 7Dipp [1, 3-bis(2, 6-diisopropylphenyl)-4, 5, 6, 7-tetrahydro-1, 3-diazepin-2-ylidene] allows the isolation of a neutral digold sulfide.